Existence of Periodic Solutions for a Class of Difference Systems with p-Laplacian - Kai Chen; Qiongfen Zhang (Abstract and Applied Analysis)
By applying the least action principle and minimax methods in critical point theory, we prove the existence of periodic solutions for a class of difference systems with p-Laplacian and obtain some existence theorems.